Effectiveness of whole course fine nursing combined with insulin pump blood glucose management on patients with diabetes mellitus combined with ischemic cerebral infarction - Xiaobin Wu; Yayuan Yang; Xiufeng Huang; Liwen Chen (Nutrition & Diabetes)
Abstract Objective To probe the effectiveness of whole course fine nursing combined with insulin pump blood glucose management on patients with diabetes mellitus (DM) combined with ischemic cerebral infarction (ICI). Methods The control group (conventional nursing plus insulin subcutaneous injection) and observation group (whole course fine nursing plus insulin pump blood glucose management) were established. General characteristics, glucose control effects, recovery of neurological and motor functions, self-care ability, health behaviors, quality of life, satisfaction, and adverse event incidence were compared in both groups. Results Serum FBG, 2hPG, and HbA1c levels and NIHSS scores reduced and FMA, ESCA, 2-DSCS, and SF-36 scores increased after the intervention in both groups, and all significantly improved in the observation group. The observation group had higher satisfaction with blood glucose monitoring and feedback, health knowledge education, disposal of unexpected situations, treatment effect and comprehensive evaluation, and lower total adverse event incidence rate during hospitalization than the control group. Conclusion Whole course fine nursing combined with insulin pump glucose management can enhance the glucose control effect, and improve the neurological and motor functions, self-care ability, health behaviors and quality of life in patients with DM plus ICI, with high satisfaction and reduced adverse event incidence.